Classroom Heterogeneity, Immigration Background, and Juvenile Delinquency in Switzerland: An Exploratory Study - Siegmunt, Olga (Journal of contemporary criminal justice, 2019)
In this article, we explore the relationship between the heterogeneity of secondary school classes and juvenile delinquency. The heterogeneity of school classes was measured by calculating the Herfindahl index of variety in students’ immigration background. The index was composed of three groups: natives, first-generation immigrants, and second-generation immigrants. Involvement in 13 forms of juvenile delinquency, committed during the last 12 months, was our independent variable. The offenses were grouped into minor, violent, and property offenses. The data analyzed the national class-based sample of seventh-, eighth-, and ninth-grade students in Switzerland (n = 4,158) and were collected in 2013 within the framework of the Third International Self-Report Delinquency Study (ISRD3). In general, it was found that juveniles are more likely to commit offenses when they attend school classes with higher heterogeneity, regardless of the nature of the heterogeneity (i.e., mixture of natives, first-generation immigrants, or second-generation immigrants). Within the bivariate analysis, the heterogeneity of school classes relates significantly to involvement in graffiti, vandalism, shoplifting, group fight, robbery, burglary, bicycle theft, vehicle theft, and personal theft. After statistically controlling for gender and school grade, effects of class heterogeneity persist for selected offenses.